(untitled) (Perner’s Contacts, 2020)
One of the most resonant topics today is quality. The quality measure of each process is the sum of its properties, which are manifested by its functionality in real-time. These characteristics include reliability, accuracy, safety, flexibility and much more. Due to the comparability and monitoring of development trends in the level of service quality, it is necessary to objectify this level through measurable quality characteristics (properties) and their subsequent evaluation. In the article, we deal with the evaluation and comparison of the level of selected quality criteria according to their perception by groups of passengers. In order to conduct research in the field, we conducted a questionnaire survey in a selected region of the public passenger transport system in the Slovak Republic, based on identifying the importance and measuring satisfaction with their implementation. Based on the research, the most important quality criteria (requirements) were identified - the accuracy of connections, passenger information, cleanliness and the driver’s behavior towards passengers. The interrelationship and significance of quality criteria are assessed through one-dimensional and multidimensional methods. The aim of the paper is to examine the differences in the perception of quality and satisfaction by individual groups of passengers (students, economically active population and pensioners), as each group has different quality requirements. If carriers and service providers want to keep passengers in the public passenger transport system, it is important that they focus on quality, identify quality requirements for specific groups of passengers and provide feedback in the form of measuring passenger satisfaction.